THE STAGE OF SCIENCE, TECHNOLOGY AND INNOVATION IN COLOMBIA - Bustamante Melo, Jesus
Latin American conutries have tried to close he gap that they have in development compared to the more advanced conuntries by implementing developmen and productivity policies in different economics sectors, for the Science, Tecnology and Innovation (STI) sector they have developed public policies, stimulus programs and support for researchers, resulting in STI Sistems made up of different institututions that energize STI activities. For Colombia, the STI state policies are currently concetrated in the Ministry oj Science and Tecnology (Minciencias), created in 2019, fomerly known as COLCIENCIAS, in this article a brief traceability of this evolution and some recomendations for the sector are made,